Study on Functional Outcomes of Adolescents after Initial Treatment of Upper Limb Fractures in a Selected District in Sri Lanka - Jayasekera, Hemali; Siritunga, Samitha; Senarath, Upul; Gill, Paramjit (Issues and Development in Health Research Vol. 5, 2021)
Background: Adolescents are most likely to suffer from injuries, which are the leading cause of morbidity and mortality. Fractures have been identified as a major consequence of injuries and fractures of the limbs significantly limit their functional capacity. It can lead to reduced productivity and quality of life of adolescent. As adolescents are among the most economically productive age groups, preventing adolescent-related injuries is an investment for a country. During the first three months after treatment, 59.5 percent of upper limb fracture patients admitted to the National Hospital in Sri Lanka struggled to conduct daily activities. Objective: To evaluate the functional outcomes of adolescents aged 10 to 19 years after receiving first treatment for upper limb fractures at government hospitals in Colombo district in Sri Lanka. Methodology: A follow-up research was conducted on 400 randomly selected adolescent victims who had upper limb fractures as a result of their injuries. After initial treatment, they were recruited from six main hospitals in Colombo district and followed up for six weeks. At six weeks, while attending follow-up clinics at their respective hospitals or at their homes, a validated and culturally accepted new tool was employed to measure their functional outcomes using a Likert scale. Results: After six weeks of treatment, 33.2 percent of 400 sufferers had good functional outcomes. Adolescents' highest mean score was for performing specific activities, such as playing, sports or recreational activities, or sewing, and this was their primary functional disability (Mean score 865.5 with standard deviation of 23.97). Conclusions and Recommendations: Adolescent fracture sufferers' rehabilitation care must be improved for them to recover quickly, as they are the country's future generation.